Prediction of Synthetic Seismograms and Accelerograms for Two-Layer Basis Beddings - Eduard Khachiyan; Levon Levonyan; Naira Egnatosyan (Journal of Architectural and Engineering Research)
A method has been developed for predicting strong ground motion displacements and accelerations, assuming that an earthquake is an instantaneous mechanical rupture of the Earth’s crust. The method uses derived theoretical formulas to calculate all three parameters of the ground motion: displacements, velocities, and accelerations during strong (with a magnitude  of M 6.0) earthquakes for any non-homogeneous (multilayer) ground beddings with various physical and mechanical characteristics – thicknesses, densities, and shear moduli – and at a certain distance from the expected earthquake’s rupture. The example provided involves the results obtained for a number of two-layer heterogeneous site variants in seismic categories I-IV at the magnitude of M=7.0 and distance of 15 km from the expected earthquake’s rupture. A comparison of the results obtained for actual heterogeneous foundation beddings with the equivalent homogeneous beddings showed divergences by 1.3-1.6 times, depending on the number of higher mode oscillations considered. Recommendations are provided for simplified calculation of seismograms and accelerograms for heterogeneous foundation beddings, with a certain correction of calculation results for equivalent homogeneous beddings.